Ganglioglioma, Epilepsy, and Intellectual Impairment due to Familial TSC1 Deletion. (June 2018) - Gilboa, Tal; Segel, Reeval; Zeligson, Sharon; Alterescu, Gheona; Ben-Pazi, Hilla
Background: Tuberous sclerosis complex (TSC) is a multisystem disorder diagnosed by clinical criteria and/or genetic testing. Genetic testing reveals atypical phenotypes that have not met clinical criteria, with practical implications. Methods: We describe 4 family members with pathogenic partial deletion in TSC1 who individually did not meet tuberous sclerosis complex clinical criteria. Results: Family members had different and atypical findings of tuberous sclerosis complex. Although none of the family members fulfilled the clinical criteria for tuberous sclerosis complex, they all carried the same genomic deletion (9q34.13q34.2) that included part of the TSC1 gene. One member had ganglioglioma and intractable seizures, one sibling presented with seizures, developmental delay, and displayed white matter abnormalities; another sibling had no clinical manifestations but has cortical tuber. Their mother has facial angiofibroma, cortical tuber, and seizures during infancy. Conclusions: Ganglioglioma may be a phenotypic expression of TSC1 . Genetic testing is recommended for infants with brain tumors, especially those with an abnormal familial history.